Sustainability And Agriculture - Flynn, Dave (Archives of Business Research, 2018)
Water resources are being threatened by farming initiatives in developing countries as well as in more advanced countries. It entails the disruption of aged soils for cultivation of palm oil emitting CO2 gases into the atmosphere. It also results from the use of fertilizers in agricultural areas in Europe and the United States. Unless significant intervention by non-government and government entities persuade for-profit enterprises to engage in significantly more sustainable agricultural practices, the availability of clean water resources will reach catastrophically low levels. Suggestions for reaching more sustainable outcomes are provided.